Inverted eruption of supernumerary tooth in the anterior maxilla- report of a rare case - R. Lakshman, A.; K. Kanneppady, Sh.; L. Castelino, R.; Balan, P. (Scientific Journal of Medical Science, 2013)
Inverted teeth have been reported in both maxilla and mandible and most of them are inverted impacted third molars and premolars. However, very few cases of intraoral inverted tooth eruption have been reported till date. A unique case of inverted supernumerary teeth between the central and lateral incisors in the maxilla is reported here.